Sistem Informasi Tagihan Listrik Unit Usaha di Area Taman Mini Indonesia Indah Berbasis Web - Wibowo, Gigih Hasoko; Yulia, Eka Rini (LPPM UNIKA Santo Thomas Medan, 2023)
The use of electricity in the Taman Mini Indonesia area is quite large every month. Electricity usage is not only used for the operations of TMII itself but is also used by business units such as stalls, partners, regional pavilions, and museums. Therefore, every month the business unit pays its electricity usage to TMII. The process of making electricity bills for business units at TMII is still manual. With the existence of a web-based electricity bill information system for business units in the TMII area, it is easier for officers to record kwh meters, which speeds up making electricity bills, and it is easier for customers to get billing data online.